Prevalence of gastrointestinal parasites in cattle in Indonesia: A meta-analysis and systematic review - Vika Ichsania Ninditya; Fitrine Ekawasti; Joko Prastowo; Irkham Widiyono; Wisnu Nurcahyo (Veterinary World)
Background and Aim: Gastrointestinal parasites (GIPs) pose a major health challenge for cattle in Indonesia. GIP infections affect the production and reproductive performance of cattle, resulting in economic losses. However, the prevalence and distribution of infections have not been comprehensively profiled at the national level. This study aimed to estimate the prevalence of GIP infections in cattle in Indonesia.